The Use of Action Research in EFL Socio-professional Context: Students-teachers’ Perceptions - Liqaa Habeb Al-Obaydi; Nashruddin; Fakhriawan Fathu Rahman; La Ode Achmad Suherman (Hasanuddin University, 2021)
The present study intends to shed light on student-teachers perceptions towards using action research in English language classes. This study aims at ensuring full understanding of the term “action research” by student-teachers, exploring their perceptions toward using it, identifying the problems that student-teachers may face in a socio-professional context in the intercourse to the use of action research, and showing if they have any future intentions to use it in their classes. Fifty students were chosen randomly from Diyala University, College of Education for Human Sciences, English Department to represents the study sample. A questionnaire of four parts that the researchers constructed was adapted as a primary study instrument. The final statistical results show that student-teachers have positive perceptions toward using action research in the English language teaching classes.